Geography of smallholders’ tractor adoptions and R&D–Induced land productivity: Evidence from household survey data in Ghana - Takeshima, Hiroyuki; Liu, Yanyan (International Food Policy Research Institute, 2019)
Despite the urbanization and gradual rise of medium-to-large scale farming sector, smallholders without substantial mechanization remain central to agriculture in countries like Ghana. Significant knowledge gaps exist on the adoptions of agricultural mechanization among smallholders for whom the scope for exploiting complementarity with land is limited. We test the hypotheses that high-yielding technologies, which potentially raise total factor productivity and also returns to more intensive farm power use, are important drivers of adoptions of agricultural mechanization among smallholders. Using the three rounds of repeated crosssectional, nationally representative data (Ghana Living Standard Surveys 2006, 2013, 2017), as well as unique tractor-use data in Ghana, and multi-dimensional indicators of agroclimatic similarity with plant- reeding locations, this paper shows that the adoption of rented agricultural equipment and tractors in Ghana has been induced by high-yielding production systems that have concentrated in areas that are agroclimatically similar to plant-breeding locations. These effects hold for mechanization adoptions at both extensive margins (whether to adopt or not) and intensive margins (how much to adopt). These linkages have strengthened between 2006 and 2010s, partly due to improved efficiency in supply-side factors of mechanization.